Peran Ekonomi, Manajemen dan Akutaansi dalam Islam Meningkatkan Kinerja Organisasi di Era Modern (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
Technological advancements and the rapid growth of globalization have fundamentally changed the way organizations conduct business activities, creating increasingly complex challenges and opportunities in both local and international markets. Organizations are now required to adapt quickly to changing consumer preferences, technological innovation, market competition, and economic uncertainty. In this environment, economics, management, and accounting have become three essential disciplines that play a crucial role in determining organizational effectiveness and long-term sustainability. Economics helps organizations understand market behavior, pricing strategies, supply and demand conditions, and macroeconomic factors that influence business performance. Management focuses on planning, organizing, leading, and controlling resources to ensure operational efficiency and goal achievement. Accounting provides reliable financial information through systematic recording, reporting, and analysis of transactions, enabling organizations to evaluate performance and maintain accountability. This study aims to analyze the relationship between these three disciplines in supporting organizational decision-making processes and improving overall performance. The research employs a literature review method by examining various recent academic books and journal articles. The findings reveal that the integration of economics, management, and accounting strengthens strategic planning, improves resource allocation, enhances financial transparency, and supports sustainable organizational growth in a highly competitive global environment.